2021
DOI: 10.2166/washdev.2021.067
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of blaTEM and tetA genes in antibiotic-resistant Escherichia coli isolates from Laguna Lake, Philippines

Abstract: Lakes are one of the sinks of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs); however, information on ARB and ARGs in lakes in the Philippines is scarce. In this study, Escherichia coli was isolated from the largest freshwater lake in the Philippines, Laguna Lake, to detect antibiotic resistance and the presence of ARGs. Broth microdilution assay (BMA) and molecular identification of five environmentally prevalent ARGs (strA, blaCTX-M, blaSHV, blaTEM, and tetA) were performed. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…The current study found that most clinical E. coli isolates were highly resistant to AMP. Our findings corroborate findings from other studies where E. coli isolates from clinical and environmental samples were highly resistant to penicillins such as AMP [ 85 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The high resistance of E. coli to ampicillin can be attributed to its potential to develop intrinsic resistance against penicillins.…”
Section: Discussionsupporting
confidence: 92%
“…The current study found that most clinical E. coli isolates were highly resistant to AMP. Our findings corroborate findings from other studies where E. coli isolates from clinical and environmental samples were highly resistant to penicillins such as AMP [ 85 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The high resistance of E. coli to ampicillin can be attributed to its potential to develop intrinsic resistance against penicillins.…”
Section: Discussionsupporting
confidence: 92%